Qualitative Content Analysis: A Case Study of a Malaysian Government Education Website - Nurdiana Azizan; Ross Smith; Vanessa Cooper; Noraizah Abu Bakar (Universiti Sains Islam Malaysia, 2024)
Content analysis is a set of qualitative methods utilized to analyse data from verbal, print or electronic communication channels. Text-based information from interviews, focus groups and open-ended survey questions can be evaluated using this method. This paper shall put forth the definition of qualitative content analysis and discuss the basic principles of its technique. The method for conducting qualitative content analysis research will then be outlined and explained. A case study of a Malaysian government education website is provided to demonstrate the application of the said method. The case study explores several critical success factors (CSFs) involved in the transfer of knowledge from the Government to targeted users via an education-based website. Fifteen interviews were conducted and 14 CSFs are identified and segregated into six thematic groups. This exercise shall provide practical guidance to the practitioners that are directly involved in the process. The identification and understanding of the CSFs would provide the much needed direction for the website administrators and content creators. They would have access to essential information that enable them to make strategic decisions related to their website's content development and delivery activities. This would then enhanced their capacity to deliver the requisite knowledge to their targeted users.